Non-Defaultable Debt and Sovereign Risk - Hatchondo, Juan Carlos (IMF Working Papers; Working Paper ;, 2014)
We quantify gains from introducing non-defaultable debt as a limited additional financing option into a model of equilibrium sovereign risk. We find that, for an initial (defaultable) sovereign debt level equal to 66 percent of trend aggregate income and a sovereign spread of 2.9 percent, introducing the possibility of issuing non-defaultable debt for up to 10 percent of aggregate income reduces immediately the spread to 1.4 percent, and implies a welfare gain equivalent to a permanent consumption increase of 0.9 percent. The spread reduction would be only 0.1 (0.2) percentage points higher if the government uses nondefaultable debt to buy back (finance a 'voluntary' debt exchange for) previously issued defaultable debt. Without restrictions to defaultable debt issuances in the future, the spread reduction achieved by the introduction of non-defaultable debt is short lived. We also show that allowing governments in default to increase non-defaultable debt is damaging at the time non-defaultable debt is introduced and inconsequential in the medium term. These findings shed light on different aspects of proposals to introduce common euro-area sovereign bonds that could be virtually non-defaultable.